Increasing packet delivery in Ad hoc On-Demand Distance Vector (AODV) routing protocol - Ahmad, Noor Azlan; K. Subramaniam, Shamala; Md. Desa, Jalil (IEEE, 2008)
Broadcasting in the route discovery and the route maintenance of Ad hoc On-demand Distance Vector (AODV) routing protocol provokes a high number of unsuccessful packets deliveries from the source nodes to the destination nodes. Studies have been undertaken to optimize the rebroadcast focused on the route discovery of the AODV. In this study, lifetime ratio (LR) of the active route for the intermediate node is introduced to increase the number of unsuccessful packets delivery. Simulation results focused on the improvement of the packet delivery in the routing protocol compared to standard AODV. The performance metrics are measured by varying the number of nodes and the speeds. The OMNET++ is used to simulate the performance of the metrics.